Pembelajaran PAI Berbasis HOTS di Era Pandemi Covid-19: Implementasi dan Tantangan Bagi Guru PAI - Abd. Muqit (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
This study aims to reveal and describe the learning of Islamic religious education HOTS-based in the Covid-19 pandemic era. Another goal is to find out the various obstacles faced by Islamic religious education teachers in implementing HOTS-based learning in the pandemic era. The method used in this research is qualitative with data collection through interviews, observation, and documentation. The location of this research is SDN 1 Sumberanyar. The acquisition data were analyzed by means of reduction, presenting the data and providing conclusions from the research findings. The result of the findings of this study is that Islamic religious education learning in the Covid-19 pandemic era tends to apply online impact on the implementation of HOTS which is less than optimal. In addition, teachers have obstacles in implementing HOTS-based Islamic religious education learning in the Covid-19 pandemic era due to several factors, the first is student constraints; second is the teacher constraint; third is the problem of school infrastructure.